Antiprotozoal Compounds from Urolepis hecatantha (Asteraceae) - Elso, Orlando G.; Clavin, María; Hernandez, Natalia; Slargata, Tomás; Bach, Hernán Gerónimo; Catalan, César A.N.; Aguilera, Elena; Alvarez, Guzmán; Sülsen, Valeria P. (Hindawi, 2022)
The dewaxed dichloromethane extract of Urolepis hecatantha and the compounds isolated from it were tested for their in vitro activity on Trypanosoma cruzi epimastigotes and Leishmania infantum promastigotes. The extract of U. hecatantha showed activity against both parasites with IC50 values of 7 µg/mL and 31 µg/mL, respectively. Fractionation of the dichloromethane extract led to the isolation of euparin, jaceidin, santhemoidin C, and eucannabinolide. The sesquiterpene lactones eucannabinolide and santhemoidin C were active on T. cruzi with IC50 values of 10 ± 2 µM (4.2 µg/mL) and 18 ± 3 µM (7.6 µg/mL), respectively. Euparin and santhemoidin C were the most active on L. infantum with IC50 values of 18 ± 4 µM (3.9 µg/mL) and 19 ± 4 µM (8.0 µg/mL), respectively. Eucannabinolide has also shown drug-like pharmacokinetic and toxicity properties.